English spelling and the computer - Mitton, Roger (Studies in language and linguistics (London, England), 1996)
English Spelling and the Computer provides a thorough examination of spelling focusing in particular on the difficulties faced by present day spellers. Most people make spelling mistakes and while word processors with spellcheckers do offer some help, they do not catch all the errors and often make inappropriate suggestions. This book looks at common errors and explains why they are made. A knowledge of the history and development is useful for understanding the problems of spelling and the difficulties spellcheckers are trying to address. The book therefore begins by examining the history of spelling and goes on to consider the arguments for and against reform. This is followed by an analysis of a large corpus of spelling errors including both the errors that people make when they do not know how to spell a word and the errors they make when they know how to spell the word but for some reason write something different.